Module teaching technology in studying chemistry - Kokibasova, G.T.; Mukhamadiyev, Ye.K.; Rahimbekova, K.T. (KSU publ., 2014)
Module teaching technology gives us opportunity to assert theoretical material by block-modules. The opportunity of applying of the modeling teaching technology on the chemistry lessons of the 10th class is considered. According to this technology the modules of the topic «Periodic table» are worked out. The methodical treatment is given. By applying this technology the quality of the lesson and interest of the students are increased.
Keywords: modular education; system education; block-modules; quality knowledge; psychologicalpedagogical direction; radioactivity